Analisis Pengaruh Sistem Informasi Pemasaran dan Strategi Penjualan Produk Terhadap Persaingan Penjualan Produk PT. Bank Agris, TBK Medan - Br Sitepu, Fahriani Astuti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The perception of the public towards the Bank will not be detached from the image attached to the bank attributed to its service to the customers, various types of products/services, and information technology capabilities will be the demand from the customers. Competition in meeting customer demands which in essence is the fulfillment of 'ease of conducting banking transactions anywhere', also drives banking technology competition. In leveraging information technology it can be said that the mature banking industry is at the forefront of making information technology a driver to support customer service, operating activities and business processes. This is intended to meet the demands of customers who are generally in dire need of convenient services, namely the availability of multiple, safe, convenient service channels with services 24 hours a day, 7 days a week throughout the year. Hence, both on the part of the Bank and the customer should be able to place themselves on the current technological advancements as well as wise in utilizing information technology. Banks require a Marketing Information System (SIP) which is a computer-based system that works together with other functional information systems to support the management of the company in solving problems related to marketing of products in order to know the needs and wants of customers, formulate the best fragrances and fragrances in the market. by customers so that the Bank’s marketing activities can be implemented and precisely targeted. Information as one of the important components in the company for the achievement of the goal of the company i.e. increasing the sale of the product.